Mendelian randomization study of micronutrients and development of CKD in a Korean population - Juyeon Lee; Sangjun Lee; Kook-Hwan Oh; Sue K. Park (Nutrition Journal)
Abstract Background Although dietary intake is a key modifiable risk factor in the development of chronic kidney disease (CKD), the optimal consumption levels to prevent CKD and the intake levels that pose the least risk remain unclear. Building on the findings from our previous cohort study, this research aims to use genetic variants as instrumental variables to clarify the complex relationship between micronutrient status and the pathogenesis of CKD. Methods Of 5,078 participants with a baseline estimate glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73 m2 and who were not diagnosed with CKD, we ascertained 708 new CKD cases over 12 year follow-up periods. Mendelian randomization analyses were conducted using genetic instrumental variables to examine the causal relationships between dietary micronutrients (Phosphorus, Vitamin B2, B6 and C) levels and the development of CKD. Results In Mendelian randomization study, using the inverse variance-weighted (IVW) radial method, dietary vitamin B6 (β = -4.016, p-value = 8.72E-05) and C (β = 2.573, p = 1.41E-05) intake levels demonstrated significant associations with the development of CKD. However, there was no significant association observed for dietary phosphorus and vitamin B2 intake levels with the development of CKD (p > 0.05). Conclusions This study found a weak causal link to genetically predicted levels of vitamins B6 and C on CKD development. Given potential residual pleiotropy and biological limitations, findings should be cautiously interpreted yet highlight the possible role of balanced micronutrient intake in kidney health.